Vientos de Yubarta hotel eco sostenible (2013)
"The architectural program seeks to organize, divide and respond to the needs that exist today. On one hand, is the community of NUQUÍ WOMEN living in the area and facing cost overruns for very poor quality utilities and disconnection with the world, all the time. On the other hand, THE TOURIST, who comes in search of new experiences and direct contact with nature and culture, high seasons. And a third actor, the NUQUÍ COMMUNITY. The lack of venues for different events (Training in the SENA, social events, city hall and corporate events, and recreational space for schools.), in low Season, complement activities offered by Vientos de Yubarta (Humpback Whales winds hotel). After learning and understanding the activities carried out by this community nowadays, the architectural response zoned and sliced up activities to meet their requirements, by locating three social stations and the project´s heart guarded in the rainforest. SOCIAL. We access the project by a dock, which leads us to a great social space equipped with a kiosk for events, a swimming pool for adults and children, terrace for rest and / or events and a more intimate restaurant, all oriented towards the Pacific ocean in a strategic point for whale watching. The second station is the thermal swimming pool, with an organic design that combines the warm waters of the hot Springs with the stream waters, supported by a basic equipment of bathrooms and sitting and waiting area. Towards the rear of this equipment, we found a small hydroelectric plant that gives an additional use to the stream of the creek. Lastly, taking advantage of the different geographical features in the highest point of the batch, we find the gazebo, which offers another visual of the Pacific Ocean, lost in the ""noise"" of trees and birds. The beaches of the Peninsula, offering different experiences according to each of the guests intention. PRIVATE. Comprised of 11 bungalows and camping area, Located in the center of activities, separated by different species of trees that create particular environments based on location, giving privacy, involving the visitor with the environment of this, but always, opening visual towards the magnificence of the Pacific Ocean.SERVICES. It is the articulation between social, the features that make the project self-sustaining and the private areas. Consisting of an entire suite of restaurants, clothes, storage areas and housing for all personnel involved in the place. Connected to the orchard and the barn which supply much of the hotel's kitchen, as well as the bio-digester, which uses large stones and thick vegetation, to complement and solve a current problem. These are the main elements of VIENTOS DE YUBARTA where by architecture is possible to provide an environmental, social and economic answer, without leaving aside the design and comfort value element created by the architect."